Evaluation of the Vertical Profile of Radio Refractivity and its Gradients in a Tropical Atmosphere - Igwe, K. C.; Tukur, M. (Journal of Advanced Industrial Technology and Application, 2023)
This paper evaluates radio refractivity and its gradients over Abuja, the Federal Capital Territory of Nigeria, using five years upper air meteorological data obtained from the Nigerian Meteorological Agency (NiMet). From the results obtained, radio refractivity was observed to decrease with increasing altitude. Also, higher refractivity values were observed in wet season, while lower values were recorded in dry season. An average refractivity value of 326 N-Units was obtained at 1 km altitude, while average refractivity gradient values of -34 N-Units/km and -40 N-Units/km were recorded for the dry and wet season months respectively. A total average value of -38 N-Units/km for refractivity gradient was obtained for the five-year study period, thus making the atmospheric condition over Abuja to be sub-refractive. The effective earth radius factor (k-factor) computed for the location was also observed to be higher in the wet season months than the dry season months. An average k-factor value of 1.32 was obtained for the study period.